Narratives of Resistance: Discursive Strategies in Nigeria’s 2020 #EndSARS Protest - Alugbin, Matthew; Iyoha, Osas (Àgídìgbo: ABUAD Journal of the Humanities, 2024)
The #EndSARS hashtag, which started in 2017, was one of the tools used to share, on Twitter, experiences and advocacy on police brutality in Nigeria. Extant works have explored the use of social media for civic engagement, consciousness re-awakening, counter-narratives and societal disruption, amongst other uses. The present study focuses on how discursive strategies of resistance were deployed to create and sustain agitations using Twitter as a mobilising force of mass movement to achieve political goals. van Dijk’s socio-cognitive model of Critical Discourse Analysis (CDA) with insights from computer-assisted textual analysis was used to analyse a corpus of 1,000 tweets with the #EndSARS hashtag. Findings show that blame attribution, recontexualisation of events, categorisation, victim positioning, and cross-border appeal are discursive resistance strategies used to sustain solidarity, create bonds and negotiate power among the marginalised people. Through these, protesters were able to create defiance and directive acts in the people. These strategies not only create a contest for political power between the government and the masses but also help in the construction of a resistance ideology among the people. Hence, new perspectives on social media should consider the paradigm shift that has resulted in how narratives are sustained and negotiated during online social movements.